2015
DOI: 10.1071/an14523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary concentrate to forage ratio and thiamine supplementation on the rumen fermentation and ruminal bacterial community in dairy cows

Abstract: Abstract.A subacute ruminal acidosis (SARA) model was induced gradually by increasing the proportion of dietary concentrate to evaluate the effect of thiamine supplementation on the structure of bacterial community in dairy cows. Three Holstein dairy cows with rumen cannula were randomly assigned to a replicated 3 · 3 Latin square design trial and received three diets during three successive 21-day periods in each square. The three dietary treatments were as follows: a lowconcentrate diet (control), a high-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 18 publications
3
53
0
2
Order By: Relevance
“…The most active form of vitamin B1 is thiamin pyrophosphate; its synthesis in eukaryotes requires thiamine pyrophosphokinase, which catalyzes pyrophosphate group transfer from ATP to thiamine (Tylicki et al, 2018). Thiamin supplementation in dairy cattle has been reported to increase rumen pH and balance the population of lactic acidproducing and -consuming bacteria (Wang et al, 2015). Thiamine is critical for cellular function, as its phosphorylated and active form, thiamine diphosphate (TDP), acts as a coenzyme for three key enzymes in glucose metabolism (Liu et al, 2017) which differs to a great extent in high and low feed efficient groups (Fu et al, 2017).…”
Section: Mtor and Mapk: Key Signaling Pathways In Durocmentioning
confidence: 99%
“…The most active form of vitamin B1 is thiamin pyrophosphate; its synthesis in eukaryotes requires thiamine pyrophosphokinase, which catalyzes pyrophosphate group transfer from ATP to thiamine (Tylicki et al, 2018). Thiamin supplementation in dairy cattle has been reported to increase rumen pH and balance the population of lactic acidproducing and -consuming bacteria (Wang et al, 2015). Thiamine is critical for cellular function, as its phosphorylated and active form, thiamine diphosphate (TDP), acts as a coenzyme for three key enzymes in glucose metabolism (Liu et al, 2017) which differs to a great extent in high and low feed efficient groups (Fu et al, 2017).…”
Section: Mtor and Mapk: Key Signaling Pathways In Durocmentioning
confidence: 99%
“…Treatments included a control diet (CON; 20% starch, DM basis), high-grain diet (HG, 33.2% starch, DM basis), and HG diet supplemented with 180 mg of thiamine/kg of DMI (HG+T). This dose of thiamine was selected based on our previous dose-response studies in dairy cows (Zhang et al, 2014;Wang et al, 2015). Thiamine (Thiamine hydrochloride, purity ≥99%; Wanrong Science and Technology Development Co. Ltd., Wuhan, China) was administered via the ruminal cannula twice daily after supplying diets.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Administration of thiamine increased pH and reduced the LPS concentrations in the rumen of HG-fed cows, and this effect could be partially due to the improvement in microbial compositions. It has been demonstrated that higher ruminal thiamine can support the protozoa population (Höltershinken et al, 2003), and thiamine supplementation significantly reduced the population of S. bovis and increased the population of M. elsdenii (Wang et al, 2015). Hence, the stabilized microbial structure by thiamine supplementation reduced the production of acids and eventually more stable ruminal pH and lower LPS from bacterial lysis.…”
Section: Effect Of Thiamine Supplementation On Ph and Lps Concentratimentioning
confidence: 99%
See 1 more Smart Citation
“…Because S. bovis is lactate producing and acid tolerant, it plays an important role in rumen acidosis (1). Our previous study with dairy cows demonstrated that under normal conditions, the population of S. bovis is small, resulting in an insignificant amount of lactate production that is quickly metabolized by lactate utilizers such as Selenomonas ruminantium and Megasphaera elsdenii (2,3). However, when a high-concentrate diet is provided, the growth rate of S. bovis increases (4).…”
mentioning
confidence: 99%